2021
DOI: 10.1038/s41598-021-99905-6
|View full text |Cite
|
Sign up to set email alerts
|

A machine-learning parsimonious multivariable predictive model of mortality risk in patients with Covid-19

Abstract: The COVID-19 pandemic is impressively challenging the healthcare system. Several prognostic models have been validated but few of them are implemented in daily practice. The objective of the study was to validate a machine-learning risk prediction model using easy-to-obtain parameters to help to identify patients with COVID-19 who are at higher risk of death. The training cohort included all patients admitted to Fondazione Policlinico Gemelli with COVID-19 from March 5, 2020, to November 5, 2020. Afterward, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 30 publications
0
15
0
Order By: Relevance
“…COVID-19 results in a systemic hypercoagulation state, producing pulmonary thromboembolisms, ischemic strokes, and other disorders, and a markedly large number patients experience severe complications. This complication can be assessed on the basis of 2 laboratory parameters: D-Dimer and platelets [ 16 , 18 ]. Most prognostic studies also identified creatinine or urea as important factors related to mortality risk.…”
Section: Discussionmentioning
confidence: 99%
“…COVID-19 results in a systemic hypercoagulation state, producing pulmonary thromboembolisms, ischemic strokes, and other disorders, and a markedly large number patients experience severe complications. This complication can be assessed on the basis of 2 laboratory parameters: D-Dimer and platelets [ 16 , 18 ]. Most prognostic studies also identified creatinine or urea as important factors related to mortality risk.…”
Section: Discussionmentioning
confidence: 99%
“…From a public health point of view, the prediction model may support optimal resource use. For instance, predictive models identify clinical criteria and laboratory values to safely allocate a person to common wards or to be discharged at home or to be de-isolated when probability of a COVID-19 diagnosis is poor [19] . This may result in saving hospital resources (beds, nurse and physician staff, personal protective equipment, disinfectant materials).…”
Section: Discussionmentioning
confidence: 99%
“…In terms of computer algorithm used, the NPL method to transform text into data is based on a hybrid approach using rules and annotations derived from medical guidelines, combined with A.I. (machine learning); in this experience, this was developed using the SAS Visual Text Analytics ® environment ( 12 , 13 ). Pre-processing steps as such as segmentation, boundary detection and tokenization, and word normalization (stemming, spelling correction, expansion of abbreviation) were performed to achieve a higher degree of accuracy.…”
Section: Methodsmentioning
confidence: 99%